PERANAN MEDIATOR HAKIM DAN MEDIATOR NON HAKIM MELINDUNGI HAK-HAK ANAK DALAM PENYELESAIAN SENGKETA PERCERAIAN - Saraswati, Rika; Hadiyono, V; Kusniati, Yuni; Boputra, Emanuel (Justitia et Pax, 2020)
Based on Supreme Court Regulation Number 1 of 2016 on the Mediation Procedurel in Court, mediation is a step that must undertaken before the court hearing process. Therefore, it is important to know the implementation of mediation in Semarang Religious Court and Semarang District Court, especially its role to resolve marriage disputes and child custody cases. The question of the study is how is the role of mediators (both judge and non-judge) in the mediation process of divorce and child custody disputes, and how the role of mediators in implementating of children's rights on the mediation process is. Data was obtained through a documentary research and distributed questionnaires to 3 (three) District Court Judges and 2 (two) Semarang Religious Court Judges, and 3 (three) mediators at Walisongo Mediation Centre (WMC). The findings demonstrated that the role of judge and non-judge mediators in the mediation process of divorce and child custody cases was only as a facilitator. The non-judge mediators held more strict principle of not giving advice in order to maintenance of their neutrality than that of the judge mediators. The mediator has implemented their role by conveying and explaining children's rights, encouraging the parties to put forward the best interests of the child, facilitating women disputant to be able to fight for themselves and their children’s interests and needs, and reminding the obligation of both parties to fulfil the needs and the cost of their children’s lives if divorce was undertaken as a final solution.